080 IIH Life A prospective longitudinal cohort study of idiopathic intracranial hypertension. Issue 9 (12th August 2022) - Thaller, Mark; Homer, Victoria; Wakerley, Benjamin; Mollan, Susan; Sinclair, Alexandra
Abstract : Introduction: There is limited longitudinal data evaluating visual and headache outcomes in Idiopathic intracranial hypertension and large prospective studies are required. Aims and Methods To evaluate the disease course for non-surgical IIH patients, determined by their pres- entation to neuro-ophthalmology with active IIH (papilloedema present) versus those in ocular remission. Data source: the prospectively collected IIH Life database (2013-2021). Loess smoothers were used to trend measurements over time. Results: 490 patients had IIH, 98% female and mean body mass index (BMI) 38 kg/m2. Visual outcomes showed little difference in Humphrey visual field mean deviation or acuity over time, despite higher optical coherence tomography (OCT) global peripapillary retinal nerve fibre layer thickness (RNFL) in the active group. For each unit increase in BMI RNFL increased by 1.21 µm. High headache frequency was found to be determined by personal migraine history and daily headache at diagnosis. Use of ICP medications did not affect visual or headache outcomes. Conclusions: OCT appears to be a better measure for disease activity than visual field and acuity. The headache burden was high in this cohort and required complex headache management. In this cohort we were unable to establish the long-term benefit from use of ICP lowering medications.